Wealth, gifts and estate planning at the end of life - David Sturrock; Stefan P. T. Groot; Jan L. Möhlmann (Institute for Fiscal Studies (IFS), 2022)
We quantify the size and tax-responsiveness of financial transfers made to heirs before death. The wealth of singles (including widows) with children declines substantially in anticipation of death. 92% of this decline is explained by transfers to children, while long-term care copayments can explain the remainder. Tax-reducing transfers are made across the wealth distribution and are very responsive to the tax rate. Using bunching and difference-in-bunching estimation and exploiting a reform to gift taxation, we estimate Frisch elasticities of gifts to the net-of-tax rate between 9, for those giving around exteuro27,000, and 1, for those giving around exteuro125,000.
Keywords: D12; D14; D64; H26; 330; Deathbed giving; inter-vivos transfers; bequests